2022
DOI: 10.1039/d2ra06121j
|View full text |Cite
|
Sign up to set email alerts
|

Two dimensional twin T-graphene: monolayer for visible-light photocatalytic water splitting and bulk for anode material of magnesium batteries

Abstract: Twin T-graphene has great potential in overall photocatalytic water splitting and as the anode material of magnesium batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Thus, constructing a monolayer sheet into a twin structure often results in opening a band gap. For instance, graphene and T-graphene are semimetals, while twin graphene and twin T-graphene are semiconductors with band gaps of 0.73–0.98 and 1.79–2.70 eV, respectively. , Therefore, the electronic properties can change significantly when two monolayer sheets are combined to form a twin structure. In the present study, twin 4–8 graphene exhibits electronic behavior which is distinct from T-graphene.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, constructing a monolayer sheet into a twin structure often results in opening a band gap. For instance, graphene and T-graphene are semimetals, while twin graphene and twin T-graphene are semiconductors with band gaps of 0.73–0.98 and 1.79–2.70 eV, respectively. , Therefore, the electronic properties can change significantly when two monolayer sheets are combined to form a twin structure. In the present study, twin 4–8 graphene exhibits electronic behavior which is distinct from T-graphene.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations believed that the honeycomb lattice was required to create Dirac cones.But new scienti c attitudes and studies evaluated the development of Dirac cones in new 2D structures, which rejected the existence of Dirac cones just in honeycomb lattices 9 .Therefore, new ndings showed that allotropes [10][11][12][13] such as E-graphene, Tgraphene, S-graphene, graphyne, D-graphene, etc. with non-hexagonal lattices have SP 2 hybridization and are thermodynamically stable, as well as the condition of existence satisfy the Dirac cones.T-graphene or tetragonal with high Fermi velocity and unique mechanical properties as well as special potential in hydrogen storage has attracted special attention.Studies on the electronic, geometrical, and physical properties of T-graphene show that this form of carbon with low density, outstanding intrinsic electronic properties, and unique structural stability is a very suitable candidate for use in making electrodes, photocatalysts [14][15][16][17] , etc. On the other hand, it has been found that the thermodynamic stability of Tgraphene is more signi cant than other 2D graphene allotropes.…”
Section: -Introductionmentioning
confidence: 99%
“…Recently, a class of 2D carbon materials like bilayers of graphene and graphyne sheets has been introduced. [44,[46][47][48][49] In these sheets named twin graphene and twin graphyne sheets, one layer is conjoined with another. The thermal and dynamical stability of twin graphene sheets are carefully verified.…”
Section: Introductionmentioning
confidence: 99%
“…[41,44,48] The interesting properties suggest that twin sheets can be attractive materials for use in semiconductor photocatalytic, battery field, mechanical, and optoelectronic nanodevices. [44,48,49,51,54,55] A new twin sheet named twin irida graphene is proposed and investigated in the current study. Calculations based on density functional theory (DFT) are used to examine its structural, mechanical, electronic, and optical properties.…”
Section: Introductionmentioning
confidence: 99%